2019
DOI: 10.1016/j.ram.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and removal ability of non-toxigenic Aspergillus section Flavi in presence of atrazine, chlorpyrifos and endosulfan

Abstract: This study evaluated the in vitro effect of three concentrations of atrazine, chlorpyrifos and endosulfan on the growth parameters of four non-toxigenic Aspergillus section Flavi strains. The ability of the strains to remove these pesticides in a synthetic medium was also determined. Growth parameters were measured on soil extract solid medium supplied with 5, 10 and 20mg/l of each pesticide, and conditioned to -0.70, -2.78, -7.06 and -10.0 water potential (MPa). Removal assays were performed in Czapek Doc med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The ability of AF to eliminate pesticides including atrazine, chlorpyrifos, and endosulfan (50%–90%) has been documented by researchers [24]. Hasanin et al [25] identified an AF GYPTA5 that has ligninolytic capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of AF to eliminate pesticides including atrazine, chlorpyrifos, and endosulfan (50%–90%) has been documented by researchers [24]. Hasanin et al [25] identified an AF GYPTA5 that has ligninolytic capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The successful strategy to further enhance the biodegradation capacities of filamentous fungi is most likely a selective adaptation of fungus on specific pesticide, or its isolation directly from the pesticide-exposed soils. The latter approach has been tested by Barberis et al [ 60 ] who reported that two Aspergillus oryzae strains, AM 1 and AM 2, isolated from soils that have been exposed to pesticides in last decade, highly varied in the ability to degrade 20 mg·L −1 chlorpyrifos after 30 days of incubation. While AM 1 strain removed 50%, the AM 2 strain removed approximately 73%.…”
Section: Degradation Of Organophosphorus Pesticides By Aspe...mentioning
confidence: 99%
“…herbicide. Barberis, Carranza, Magnoli, Benito, and Magnoli (2018) indicated that Aspergillus oryzae was tolerant to high atrazine levels and may be considered a potential bioremediation agent. The fungus A. fumigatus was tolerant to all changes that occurred in this study.…”
Section: Maximum Inhibitionmentioning
confidence: 99%